Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome